Potential Biological Hazards in Health Clinics: Key Strategies for Enhancing Worker Safety in Malaysia - Ahmad, Subki; Awang, Normah; Abdull Hamid, Ermie; Ithnin, Anuar; Kamaludin, Nurul Farahana; Muhd Nor, Noraizah (UI Scholars Hub, 2025)
Background: Biological hazards in health clinics may lead to acute or chronic health issues for healthcare workers. This study aims to identify potential biological hazards within health clinics, with a focus on the knowledge, attitude, and practice (KAP) of healthcare workers, in order to improve their safety. Methods: Samples from environmental surfaces were collected and cultured to identify bacterial pathogens. A cross-sectional study involving 203 healthcare workers was conducted using a questionnaire derived from CDC-adapted guidelines. Descriptive analysis and multivariate regression were used to assess KAP. Results: Bacterial growth was observed in all clinics. The Kruskal-Wallis Test indicated significant differences in Aerobic Colony Count across sampling sites, but not between clinics. Healthcare workers demonstrated good knowledge and attitudes but exhibited poor practices, mainly influenced by management responsibilities rather than individual actions. Pearson correlations revealed a very weak correlation between knowledge and practices, as well as between attitude and practices. Regression analysis indicated that higher practice scores were predicted by the workers' occupations. Conclusions: Biological hazards were found in all clinics, and poor practices had a greater significant impact on safety than a lack of knowledge or negative attitudes. Mandatory training, real-time audits, strict rules, and enhanced monitoring are essential strategies for improving worker safety.